Individual traceability of Iberian pigs: electronic identification and validation using molecular markers - Rodríguez C.; García-Casco J.; Alves E. (5. International Symposium on the Mediterranean Pig, 2007)
Full traceability in the animal food supply chain is increasingly demanded by consumers as an essential tool for monitoring food safety and quality. Traditional tagging systems present several disadvantages in Iberian pigs because of their production system. A critical aspect of electronic identification is the injection site, because transponders will migrate in the fat tissues in heavy pigs. More than 1700 Iberian piglets were injected intraperitoneally with numbered transponders. Two biological samples (blood from the piglets and fresh meat samples from the carcasses) were used to test individual traceability. Preliminary results showed that only 3.58% of the transponders were not detected at the slaughterhouse. 99% of the detected devices were found at the abdominal cavity and the remaining 1% was found on the carcasses. The validation of the two biological samples, made using a panel of 8 microsatellites, showed a total agreement between the two kinds of samples.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)